Neutrophil extracellular traps drive dacryolithiasis - Zlatar, Leticija; Timm, Thomas; Lochnit, Günter; Bilyy, Rostyslav O.; Bäuerle, Tobias; Munoz-Becerra, Marco; Schett, Georg; Knopf, Jasmin; Heichel, Jens; Javed Ali, Mohammad; Schapher, Mirco Lothar; Paulsen, Friedrich; et al. (Cells, 2023)
mucopeptide concretions; dacryoliths; dacryolithiasis; lacrimal sac; neutrophils; neutrophil extracellular traps